IMPACT ASSESSMENT OF TOURISTIFICATION IN YOGYAKARTA ON THE DEVELOPMENT OF URBAN AND RURAL TOURIST VILLAGES - Heru Purboyo Hidayat Putro; Shinta Permana Putri (Centre For Tourism Planning and Development, 2019)
The explosion of tourism activities encourages urban development initiatives. The phenomenon is known as 'touristification'. The phenomenon of touristification in the city of Yogyakarta is interesting to study, in order to examine its characteristics. The method used in this study is qualitative with data collected online. The findings of this study are the first, namely the development of tourist villages as a result of the growth of tourism activities, especially in the Malioboro area and its surroundings as the primadonna of tourism activities in the city of Yogyakarta. The development of tourist villages also helped to stimulate tourism supporting businesses engaged in accommodation. As a result, many residential neighbourhoods were transformed into residential facilities for overnight tourists. With the alternative forms and locations of this lodging, tourism activities in the city of Yogyakarta are not only concentrated in the city centre. Rural areas also transformed into a tourist area, which plays as a supporting region. The emergence of a tourist village is considered to have the opportunity to introduce and enhance existing local potential.